Paramedic Self-reported Exposure to Violence in the Emergency Medical Services (EMS) Workplace: A Mixed-methods Cross-sectional Survey. (2nd October 2014) - Bigham, Blair L.; Jensen, Jan L.; Tavares, Walter; Drennan, Ian R.; Saleem, Humaira; Dainty, Katie N.; Munro, Glenn
ABSTRACT Introduction. Studies from Australia, Sweden, the United States, and elsewhere have found that paramedics experience violence in the emergency medical services (EMS) workplace. The objective of this study was to describe and explore violence experienced by paramedics in the ground ambulance setting, including types of violence experienced, by whom the violence was perpetrated, actions taken by paramedics, and effects of these episodes. Method. A cross-sectional study utilizing a mixed-methods paper survey was provided to a convenience sample of rural, suburban, and urban-based ground ambulance paramedics in two Canadian provinces. Paramedics were asked to describe episodes of verbal assault, intimidation, physical assault, sexual harassment, and sexual assault they were exposed to during the past 12 months. Qualitative questions inquired about the impact of these experiences. Response selections were analyzed using descriptive statistics and regression analysis, and qualitative data was analyzed using descriptive content analysis. Results. A total of 1, 884 paramedics were invited to participate and 1, 676 responded (89.0%). Most participants (75%) reported experiencing violence in the past 12 months. The most common form of violence reported was verbal assault (67%), followed by intimidation (41%), physical assault (26%), sexual harassment (14%), and sexual assault (3%). Patients were identified as the most common perpetrators of violence. Serious sequellae were qualitatively reported. Conclusion. The majority of Canadian paramedics surveyed experience violence in the workplace, which can lead to serious personal and professional sequellae. Strategies should be devised and studied to reduce violent events toward paramedics and to mitigate the impact such events have on the wellbeing of paramedics.